Tax haven investors and corporate profitability: Evidence of profit shifting by German-based affiliates of multinational firms - Sarah Godar (Charles University in Prague, Institute of Economic Studies (IES), 2018)
This paper uses confidential firm-level panel data to provide new estimates on the extent of corporate profit shifting by German-based affiliates of multinational corporations. The estimated semi-elasticity of reported profits with regard to statutory foreign tax rates is 3.6, or 4.8 when allowing for a non-linear relationship. This is higher than most of the previous estimates of around 1. The case for a non-linear relationship is even stronger when average effective tax rates are used instead of statutory rates. In addition, the paper develops an alternative identification strategy suggesting that the first-time appearance of a tax-haven investor in the ownership chain reduces the reported profits of German-based affiliates by 61 percent if a majority of the affiliate is held by a single investor. The estimated effects are used to extrapolate the amount of shifted profits and associated revenue losses for all German-based foreign affiliates. The results suggest moderate but non-negligible revenue losses between 2.9 and 10.7 percent of corporate income tax revenues (or EUR 1.5-5.6 bn in 2015).
Keywords: 330; Gewinnverlagerung; Steueroase; Ausländische Tochtergesellschaft; Multinationales Unternehmen; Panel; Deutschland